Growth and Value Effect on Jakarta Islamic Index: Analysis towards Performance of Sharia Equity Mutual Fund - Sylva Alif Rusmita; Marhanum Che Mohd Salleh (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2019)
This study provides evidence that value and stocks’ growth able to explain Net Asset Value of Shariah Mutual Fund. It is important for investment managers and investors to estimate future profit or loss that may happen on their mutual funds prior they venture into the investment platform. This study therefore is conducted to prove that factors including value and growth may affect the future profit of Shariah Mutual Funds. Based on quantitative analysis with secondary data from companies indexed in the Jakarta Islamic Index and Sharia Mutual Fund from year 2013 to 2017, it is found that both growth and value of stock have equally affected the profit of Sharia Mutual Funds. In addition, growth of stock has a larger R-Square than its value which means that the investors or fund managers would need to observe the stock growth more often than its value in order to predict future profitability of Shariah funds. It is expected that the results of this study can provide additional insight to investment managers when choosing a portfolio for investors. For investors, this information is useful to predict the risk and return that they will receive from the investment.